Detection of Deformed Number Plates in Natural Scene Images - Manasa, Chiyyedu; Pooja, N; S, Sushmitha; Monisha, R; Deepika, C (International Journal of Computer Sciences and Engineering, 2021)
Automatic license plate detection is one of the most common video analytics. Existing system fails if the license plate is deformed (broken or blurred). The main cause for the deformation of the number plate is when the vehicle met with an accident or whenever car robbery takes place. Recognizing various disfigured numbers on deformed number plates has been one of the challenging issue in the field of research. This paper concentrates on deformed number plate detection and recognition. Here MATLAB software is used to extract the alphanumeric values which is deformed. Template matching being the oldest method has been used to recognize the alphanumeric values. Our algorithm has been applied on various types of number plates and achieved an accuracy of 78% for the deformed number plates. This study has importance in various real world applications like traffic control, toll control or parking lot access.